Ryanodine Receptors Structure, function and dysfunction in clinical disease - Wehrens, Xander H. T.; Wehrens, Xander H. T.; Marks, Andrew R.; Marks, Andrew R. (Developments in Cardiovascular Medicine,, 2005)
In recent years, the ryanodine receptor has emerged as a new and very promising target for the treatment of several cardiovascular disorders, including cardiac arrhythmias and heart failure. This volume is the most current publication devoted to the major intracellular calcium-release channel, the ryanodine receptor. "In this series of brief but informative chapters, the contributions progress from the basic gene family and primary structure, through its 3D structure so far, to its regulation and physiology." David E. Clapham, MD, PhD Professor of Neurobiology and Pediatrics Harvard Medical School Dr. Xander H.T. Wehrens received his M.D. and Ph.D. degrees from Maastricht University in the Netherlands. His research has mainly concentrated on molecular mechanisms of cardiac arrhythmias, in particular in the setting of inherited arrhythmogenic syndromes and congestive heart failure. This work has led to the development of novel anti-arrhythmic therapies. He is currently a research scientist in the Department of Physiology and Cellular Biophysics at the College of Physicians and Surgeons of Columbia University. Dr. Andrew R. Marks is the Chair and Professor of the Department of Physiology and Cellular Biophysics at Columbia University College of Physicians and Surgeons. Dr. Marks' research has focused on understanding how macromolecular signaling complexes regulate ion channel function in muscle and non-muscle systems, and on the regulation of vascular smooth muscle proliferation and migration. His work has contributed new understandings of fundamental mechanisms that regulate muscle contraction that have lead to the discovery of molecular defects that contribute to heart failure and fatal cardiac arrhythmias.